When and Why Does Materialism Relate to Employees’ Attitudes and Well-being: The Mediational Role of Need Satisfaction and Need Frustration - Unanue, Wenceslao; Rempel, Konrad; Gómez, Marcos E.; Van den Broeck, Anja (Frontiers in Psychology, 2017)
Materialistic values may be detrimental for people’s well-being. However, we know little about why (i.e. explaining mechanisms) and when (i.e. boundary conditions) this is the case. Although low satisfaction of the psychological needs is said to play a key role in this process, a recent meta-analysis indicates that the explaining power of need satisfaction is limited and suggests that need frustration may be more important. Moreover, although materialism may be detrimental in some life domains, studies in materialistic contexts such as work are lacking, particularly in the non-Western world. In response, we put need frustration to the fore and examine both need satisfaction and frustration as the underlying processes in the relation between materialism and employee attitudes and well-being in two Latin-American countries. The Chilean sample (N = 742) shows that materialism at work is associated with less positive (work satisfaction and engagement) and more negative (burnout and turnover intentions) outcomes, even when controlling for workers’ income. Notably, need frustration explained the detrimental effects of materialism alongside need satisfaction in a unique manner, showing that it is essential to distinguish both constructs. Results were replicated in Paraguay (N = 518) using different positive (organizational commitment and meaning at work) and negative (negative emotions and job insecurity) outcomes, adding to the generalizability of our results across samples of different nations.